IL-27 expression regulation and its effects on adaptive immunity against viruses - Andres-Martin, Fernando; James, Cooper; Catalfamo, Marta (Frontiers in Immunology, 2024)
IL-27, a member of the IL-6/IL-12 cytokine superfamily, is primarily secreted by antigen presenting cells, specifically by dendric cells, macrophages and B cells. IL-27 has antiviral activities and modulates both innate and adaptive immune responses against viruses. The role of IL-27 in the setting of viral infections is not well defined and both pro-inflammatory and anti-inflammatory functions have been described. Here, we discuss the latest advancements in the role of IL-27 in several viral infection models of human disease. We highlight important aspects of IL-27 expression regulation, the critical cell sources at different stages of the infection and their impact in cell mediated immunity. Lastly, we discuss the need to better define the antiviral and modulatory (pro-inflammatory vs anti-inflammatory) properties of IL-27 in the context of human chronic viral infections.